Influence of Micro-nano Bubbles on Aerosol Pool Scrubbing Performance - CHEN Yuqi1, LIANG Hui1, , MA Qianchao2, YUAN Wanhang1, WANG Kunjun3, WANG Yansong1, HOU Yuxuan1, GU Haifeng1, SUN Zhongning1 (Yuanzineng kexue jishu)
During a nuclear severe accident, micro-nano radioactive aerosol particles will be generated and discharged into the suppression pool with high pressure gas, and then remain in the pool water under the mechanism of pool scrubbing, so as to achieve the purpose of preventing radioactive leakage. Previous studies show that the aerosol pool scrubbing efficiency curve presents a U-shaped distribution, and when the aerosol particle size is within 0.1-1 μm, the pool scrubbing efficiency is the lowest. In order to improve the pool scrubbing efficiency of aerosols in the above particle size range, the advantages of micro-nano bubbles in environmental treatment which can efficiently remove environmental impurities were learned in this study, and an experiment on the pool scrubbing efficiency of aerosol in micro-nano bubble water was carried out. By setting a control experiment, the difference between the basic characteristics of micro-nano bubble water and deionized water was first studied, and then aerosol-containing gas was injected into the deionized water and micro-nano bubble water respectively, and the removal efficiency of aerosol pool scrubbing in the two pool washing liquids was compared and analyzed, so as to explore the influence of micro-nano bubbles on the removal characteristics of aerosol pool scrubbing. The experimental results show that the micro-nano bubbles can reduce the contact angle between the pool scrubbing liquid and the solid surface, increase the negative zeta potential of the pool scrubbing liquid, and make the aerosol more easily penetrate the gas-liquid interface into the liquid phase. At the same time, the size of conventional bubbles in micro-nano bubble water is smaller, and the number of conventional bubbles leaving the nozzle per unit time increases, so that the conventional bubbles in micro-nano bubble water have a larger specific surface area and can stay in the liquid phase for a longer time. These changes make the removal efficiency of aerosol particles in the particle size range of 0.25-1 μm in micro-nano bubble water significantly improved. This study can provide experimental basis and theoretical basis for the design and optimization of aerosol pool scrubbing system.